Temporal trends in shoreline dynamics with forecasting and coastal vulnerability assessment of kuakata area, Bangladesh - Chowdhury, M Z R; Nayon, Md Helal (Bangladesh Journal of Scientific and Industrial Research, 2025)
This study examines the spatiotemporal dynamics of shoreline changes along the Kuakata coast, Bangladesh, over a 30-year period (1991–2021), using geospatial techniques and remote sensing data. Multi-temporal Landsat imagery, including Landsat7ETM, Landsat7ETM+, Landsat8, and 9(OLI), and the Digital Shoreline Analysis System (DSAS) were employed to quantify rates of erosion, accretion, and overall shoreline movement. The highest erosion rate was observed in the central BC part (-13.8 m/year), while the southeastern zone exhibited the highest accretion rate (+25.58 m/year). The total land loss and gain during the study period were calculated at 8 km² and 4.7 km², respectively. Temporal analysis revealed average shoreline movements of -9.68 m/year (1991–2000), -0.98 m/year (2000–2010), and +2.1 m/year (2010–2021). Erosional rates for these periods averaged -13.11 m/year, -6.42 m/year, and -8.38 m/year, while accretion rates were 15.09 m/year, 14.73 m/year, and 18.56 m/year, respectively. Our findings provide actionable insights into erosion mitigation and sustainable coastal management strategies for one of Bangladesh's most dynamic and vulnerable shorelines. Bangladesh J. Sci. Ind. Res. 60(3), 169-182, 2025